2019
DOI: 10.3390/foods8090410
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional Biosurfactant Extract Obtained from Corn Steep Water as Bactericide for Agrifood Industry

Abstract: The increase of crop production along with stricter requirements on food security have augmented the demand of new and eco-friendly bactericides. Most of the bactericides used at the moment consist of persistent organic substances, representing a risk for environmental and human health. For instance, agriculture bactericides used for crop protection includes copper-based, dithiocarbamate and amide bactericides, which are not biodegradable, resulting in the necessity of further research about the production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
4
18
0
Order By: Relevance
“…Regarding its physico-chemical characteristics, the biosurfactant extract from the CSW revealed its ability to reduce the surface tension of water to a minimum value of 43.8 mN/m, which is in concordance with the results shown in previous studies [12,15,21]. Additionally, the CMC obtained for the biosurfactant extract was 306.5 mg/L.…”
Section: Biosurfactant Characterizationsupporting
confidence: 89%
See 3 more Smart Citations
“…Regarding its physico-chemical characteristics, the biosurfactant extract from the CSW revealed its ability to reduce the surface tension of water to a minimum value of 43.8 mN/m, which is in concordance with the results shown in previous studies [12,15,21]. Additionally, the CMC obtained for the biosurfactant extract was 306.5 mg/L.…”
Section: Biosurfactant Characterizationsupporting
confidence: 89%
“…Additionally, the CMC obtained for the biosurfactant extract was 306.5 mg/L. Regarding the elemental analysis, the N, C, H, and S content showed that C was the element present in the highest proportion with 43.67%, while the contents of N, H, and S were 0.77%, 5.89%, and less than 0.30%, respectively, all of which are in the range of values of previous analysis performed on biosurfactants from CSW [21].…”
Section: Biosurfactant Characterizationsupporting
confidence: 50%
See 2 more Smart Citations
“…Biosurfactants are molecules of biological origin (e.g., microorganisms) capable of reducing the surface and interfacial tensions. The surfactant activity of these natural compounds is due to the existence of both hydrophilic and hydrophobic moieties in the molecular structure (Rane et al, 2017;López-Prieto et al, 2019). Biosurfactants have aroused considerable interest in recent decades due to their advantageous properties over synthetic surfactants, such as high selectivity and biodegradability, stability in a range of environmental conditions (temperature, pH, and salinity), and low toxicity, favoring their application in the recovery of hydrophobic compounds and as emulsifiers in the pharmaceutical, cosmetic, and food industries (Garg and Priyanka, 2018;Felix et al, 2018).…”
Section: Introductionmentioning
confidence: 99%